Caveats on the Problem of Understanding Peirce's Semiotics and Pragmatism - San Juan, E., Jr. (Archīum Ateneo, 2024)
“Caveats” is San Juan’s response to “Addendum” in which he praises Stecconi’s focus on Peirce’s theory of knowledge rather than merely on his linguistic paradigm. San Juan, however, disagrees with Stecconi for “conflating the various pragmatisms into one lump.” San Juan prefers to regard Peirce as “a moderate realist” and reiterates the potential relevance of Pierce’s semiotics to the global war on terrorism and the Sri Lankan civil war.